An Assessment of Continuous Modeling for Robust Design Flood Estimation in Urban Environments - Ball, James E. (Frontiers in Earth Science, 2020)
Catchment management is a complex task that, over the past decade, has become increasingly important to the community. This is particularly the case for urban environments. Of the many catchment management issues, estimation of the magnitude and likelihood of flood events is one that remains an issue. Data is an essential component of any approach for estimation of the magnitude and likelihood of design flood characteristics. This data can be obtained from both catchment monitoring and catchment modelling with these data sources being complementary rather than competitive. However, the absence of monitored data in urban environments has resulted in the data being obtained predominantly from the use of catchment modelling. A number of alternative approaches for catchment modelling have been developed; these approaches can be categorised as either single event or continuous models. The philosophical basis behind the use of a continuous modelling approach is the concept that the model predictions will replicate the data that would have been recorded if catchment monitoring were to be undertaken at that location and for the modelled catchment conditions. When using this philosophy, a modeller must determine when the predicted data suitably replicates the true data. Presented herein is an analysis of continuous and event modelling undertaken for design flood estimation in an urban catchment located in Sydney, Australia where monitored data is available to assess the utility of the catchment model. It will be shown that frequency analysis of the predicted flows from the continuous model more closely resemble the frequency analysis of the recorded data.